Estimating the Impact of Workplace Bullying: Humanistic and Economic Burden among Workers with Chronic Medical Conditions. (18th October 2015) - Fattori, A.; Neri, L.; Aguglia, E.; Bellomo, A.; Bisogno, A.; Camerino, D.; Carpiniello, B.; Cassin, A.; Costa, G.; De Fazio, P.; Di Sciascio, G.; Favaretto, G.; et al.
Abstract : Background . Although the prevalence of work-limiting diseases is increasing, the interplay between occupational exposures and chronic medical conditions remains largely uncharacterized. Research has shown the detrimental effects of workplace bullying but very little is known about the humanistic and productivity cost in victims with chronic illnesses. We sought to assess work productivity losses and health disutility associated with bullying among subjects with chronic medical conditions. Methods . Participants (N = 1717 ) with chronic diseases answered a self-administered survey including sociodemographic and clinical data, workplace bullying experience, the SF-12 questionnaire, and the Work Productivity Activity Impairment questionnaire. Results . The prevalence of significant impairment was higher among victims of workplace bullying as compared to nonvictims (SF-12 PCS: 55.5% versus 67.9%, p < 0.01 ; SF-12 MCS: 59.4% versus 74.3%, p < 0.01 ). The adjusted marginal overall productivity cost of workplace bullying ranged from 13.9% to 17.4%, corresponding to Italian Purchase Power Parity (PPP) 2010 US 4182–5236 yearly. Association estimates were independent and not moderated by concurrent medical conditions. Conclusions . Our findings demonstrate that the burden on workers' quality of life and productivity associated with workplace bullying is substantial. This study provides key data to inform policy-making and prioritize occupational health interventions.